Gestión del cuidado en enfermería (2000)
ABSTRACT: This article suggests three strategies for an operative and structural development of nursing care management in third level hospitals, different from the administrative restructuring. These are as follows: 1) Teamwork for continuous improvement, 2) systematic evaluation, auditing, and 3) scientific and technical support with nurses in internal control. An integral program is proposed on care, nursing process and care quality courses for nurses and clinic nucleus faculty. Finally, interlocutory strategies between nurses and the faculty are stated in order to qualify care actions and to adjust the curriculum.